Drivers of economic growth: The special case of Sub-Saharan Africa - Helena Helfer (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2022)
While global studies on drivers of economic growth are useful to derive global tendencies, a more insightful analysis that leads to explicit policy implications is possible when investigating smaller entities. In this study, we focus on a panel of 40 African countries located in the Sub-Saharan region. The panel covers the times period from 1995 to 2016. We combine data on institutions with data on economic growth in order to determine which institutions are especially conductive to growth. Our analysis is framed by the approach of a hierarchy of institutions in which political institutions provide a framework in which contemporary political, economic and societal institutions develop and foster economic growht. This framework provides a solid foundation for empirical analysis and allows for multi-facetted interpretation. We find that political institutions, and among them political rights and civil liberties, are the most conductive to economic growth in the region.
Keywords: H00; O11; O43; P51; 330; Economic Growth; Institutions; Sub-Saharan Afric